2019
DOI: 10.1080/10717544.2019.1662513
|View full text |Cite
|
Sign up to set email alerts
|

Albumin-bioinspired iridium oxide nanoplatform with high photothermal conversion efficiency for synergistic chemo-photothermal of osteosarcoma

Abstract: Protein-based nanocarriers with inherent biocompatibility have been widely served as building blocks to construct versatile therapeutic nanoplatforms. Herein, bovine serum albumin-iridium oxide nanoparticles (denoted BSA-IrO2 NPs) are successfully synthesized via one-step biomineralization approach. The BSA-IrO2 NPs exhibits uniform size (40 nm), superb biocompatibility and high drug loading capacity for doxorubicin (27.4 wt%). Under near-infrared (NIR) laser irradiation, the as-prepared BSA-IrO2 NPs exhibited… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(21 citation statements)
references
References 42 publications
0
18
0
Order By: Relevance
“…The application of iridium oxide (IrO 2 ) has recently drawn attention due to its high biocompatibility and photothermal conversion efficiency [ 32 ]. Studies have discovered that IrO 2 has catalase (CAT)-like activity that enables it to catalyze H 2 O 2 in the TME to generate endogenous O 2 , thereby enhancing the efficiency of PDT [ 33 ].…”
Section: Introductionmentioning
confidence: 99%
“…The application of iridium oxide (IrO 2 ) has recently drawn attention due to its high biocompatibility and photothermal conversion efficiency [ 32 ]. Studies have discovered that IrO 2 has catalase (CAT)-like activity that enables it to catalyze H 2 O 2 in the TME to generate endogenous O 2 , thereby enhancing the efficiency of PDT [ 33 ].…”
Section: Introductionmentioning
confidence: 99%
“…Gu et al . 82 reported a bovine serum albumin-bioinspired iridium oxide nanosystem for chemophotothermal therapy of osteosarcoma. This nanosystem displayed both NIR light and pH-responsive DOX release profiles in vitro , which enhanced the therapeutic anticancer effect.…”
Section: Discussionmentioning
confidence: 99%
“…In this review three studies were identified which utilized osteosarcoma cell xenograft models to assess the PTT performance of a number of candidate formulations in vivo (Table 10). In these investigations bioactive glass scaffolds functionalized by the CuFeSe 2 nanocrystals, [ 125 ] doxorubicin‐loaded bovine serum albumin–iridium oxide NMs [ 126 ] and black phosphorus reinforced 3D‐printed scaffold [ 127 ] all exhibited complete abolition of the tumors with very little adverse side effects. The experimental detail of all relevant studies relating to bone cancer are summarized in Table 10.…”
Section: Nanomedicines Designed For Targeting and Treatment Of Cancersmentioning
confidence: 99%